Prostatic cyst in autosomal recessive polycystic kidney disease: A case presentation and literature review - Ketty Bai; Niccola B. Lynch; Christina P. Carpenter (Urology Case Reports)
Prostatic cysts are common in the adult male population with intervention of these cysts typically reserved for symptomatic patients. However, current literature is limited on the diagnosis and management of prostatic cysts in the pediatric population. We report the case of a 13-year-old boy with autosomal recessive polycystic kidney disease (ARPKD) who presented with an incidentally discovered prostatic cyst. This is the first known case report to highlight the clinical presentation, diagnosis, and management of an asymptomatic prostatic cyst in ARPKD.